YOUNG LEARNERS' VOCABULARY IMPROVEMENT THROUGH AUDIOVISUAL BY USING YOUTUBE VIDEOS :A Case Study at EEP English Course in Bandung, West Java - Sadikin, Irma Savitri (2011)
This study aims to investigate what young learners' learning principles are observed in YouTube video, the effect of YouTube video in developing their vocabulary mastery, and young learners respond to the YouTube video during the learning process. The study used a case study research design conducted in one English course in Bandung, involving 11 participants. The data, then, were collected and analyzed through triangulation data sources: vocabulary test, classroom observation, journal response, and interview. The results of this study revealed that the materials presented in YouTube videos fit young learners' learning principles. YouTube video is also effective in teaching English vocabularies. It can be seen from the improvement of students' vocabulary scores between pre- and post-test. In general the students responded positively in the form of watching videos attentively and taking part in activities. It is recommended that YouTube videos are used in EFL classroom as a supplementary activity or at home for home learning.